Novel and potent Lewis acid catalyst: Br2-catalyzed Friedel–Crafts reactions of naphthols with aldehydes. Issue 4 (16th February 2016) - Liang, Deqiang; Li, Jingjing; Li, Yanni; Wang, Baoling; Cheng, Ping; Luo, Sha
ABSTRACT: A discovery that the inexpensive Br2 can serve as a potent Lewis acid catalyst for bis(2-hydroxy-1-naphthyl)methanes synthesis is presented. Under the catalysis of Br2 at room temperature, naphthols reacted smoothly with various aldehydes with high efficiency and broad substrate scope. This reaction used to require highly acidic conditions and/or high temperature and/or pressure, and sometimes featured poor yields. Moreover, theoretical calculations suggested that Br2 is a potent Lewis acid to activate the carbonyl group, yet it was not the primary cause for the remarkable activity of Br2 in the current communication. GRAPHICAL ABSTRACT: